Surface Gradients in Dissolved Organic Matter Absorption and Fluorescence Properties along the New Zealand Sector of the Southern Ocean - D'Sa, Eurico J.; Kim, Hyun-cheol (Frontiers in Marine Science, 2017)
The Southern Ocean plays a critical role in global carbon cycling; dissolved organic matter (DOM), a component in the carbon cycle, can be characterized optically. Sea surface chromophoric dissolved organic matter (CDOM) absorption and fluorescence properties were examined in the New Zealand sector of the Southern Ocean (NZSSO) along a transect encompassing various hydrographic fronts associated with the Antarctic Circumpolar Current (ACC) during summer. Phytoplankton chlorophyll, dissolved organic carbon (DOC) and CDOM absorption were observed to be most elevated off the New Zealand shore and then decreased to low values (chlorophyll: 0.21 ± 0.06 mg m-3; DOC: 54.19 ± 4.02 μM; and CDOM absorption coefficient at 325 nm (ag325): 0.097 ± 0.061 m-1) between the Subtropical (STF) and Antarctic Polar (APF) Fronts. Increases in phytoplankton biomass and DOC concentrations between the fronts were associated with meanders or eddies observed in satellite sea surface salinity and chlorophyll imagery. Overall, CDOM absorption was the dominant contributor to total absorption at 443 nm with implications for ocean color. Beyond the APF in the Antarctic Zone, an elevated chlorophyll band likely associated with upwelled waters transitioned to low chlorophyll in the summer ice edge zone that influenced DOM optical properties. A latitudinal increase in ag325 and corresponding decrease in spectral slope S (µm-1) poleward from the STF could be due to the a number of factors including, decreasing CDOM photooxidation, upwelling of high-CDOM waters or bacterial CDOM production in the Antarctic Zone. Parallel factor (PARAFAC) analysis of fluorescence spectra identified two protein-like (C1 and C2) and two humic-like (C3 and C4) components common in the global ocean. ag325 and the humic-like C4 fluorescent component, were positively correlated to chlorophyll indicating biological control. Surface distribution of the protein-like C1 and C2 and the marine humic-like C3 components showed patterns that appeared to be influenced by both physical and biological processes. This study provides insights into surface CDOM optical properties and its transformation along a complex topographically influenced sector of the Southern Ocean that could be used to trace changes linked to the meridional overturning circulation. I